PERAN APLIKASI OK AL-IKHLASH DALAM MENINGKATKAN EFISIENSI PENGELOLAAAN KEUANGAN SANTRI PONDOK PESANTREN MODERN AL-IKHLASH - Nuraini Laila Sari; Mia Lasmi Wardiyah (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze the role of the Ok Al-Ikhlash application in improving the efficiency of financial management for students (santri) at Pondok Pesantren Modern Al-Ikhlash. Prior to the implementation of this application, financial administration processes were carried out manually, which often led to several problems such as long queues, delays in financial recording, and a lack of transparency between the administration and the students’ guardians. Using a qualitative approach with a case study method, data were collected through interviews, observations, and documentation involving the finance department, student guardians, and students. The findings indicate that the Ok Al-Ikhlash application has successfully enhanced the efficiency, transparency, and accountability of financial management within the pesantren. Financial transactions such as balance top-ups, tuition fee payments, and savings records can now be processed digitally and in real time, minimizing human errors and accelerating administrative services. Moreover, the adoption of a cashless system through student cards fosters independence, discipline, and financial responsibility among students. Overall, the Ok Al-Ikhlash application contributes significantly to the modernization of pesantren financial management through digital technology integration.